2000
DOI: 10.1016/s0925-4773(00)00366-x
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related peptide is involved in protection against invasion of tooth germs by bone via promoting the differentiation of osteoclasts during tooth development

Abstract: In order to elucidate the role of parathyroid hormone-related peptide (PTHrP) in tooth development, we treated tooth germ explants of mouse molars with antisense phosphorothioate-oligodeoxynucleotide (ODN) against PTHrP. Antisense ODN-treatment of the explants resulted in the invasion of the tooth germs by bone. The number of tartrate-resistant acid phosphatase (TRAP)-positive cells around the tooth germs in antisense ODN-treated explants was much lower than that of the control explants. Electron microscopic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…Therefore, we have used the antisense technique and examined cultured tooth germs of incisors to analyze the function of dHAND in incisor development. The antisense technique has been shown to be an effective method for investigating the function of molecules involved in tooth development, including epidermal gowth factor (Kronmiller et al 1991;Shum et al 1993), amelogenin (Diekwisch et al 1993), transforming growth factor-2 (Chai et al 1994), hepatocyte growth factor (Tabata et al 1996), and parathyroid hormone-related peptide (Liu et al 2000). Using an in ovo culture system, Srivastava et al (1995) have shown that treatment with antisense ODNs against dHAND and eHAND simultaneously affect heart looping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we have used the antisense technique and examined cultured tooth germs of incisors to analyze the function of dHAND in incisor development. The antisense technique has been shown to be an effective method for investigating the function of molecules involved in tooth development, including epidermal gowth factor (Kronmiller et al 1991;Shum et al 1993), amelogenin (Diekwisch et al 1993), transforming growth factor-2 (Chai et al 1994), hepatocyte growth factor (Tabata et al 1996), and parathyroid hormone-related peptide (Liu et al 2000). Using an in ovo culture system, Srivastava et al (1995) have shown that treatment with antisense ODNs against dHAND and eHAND simultaneously affect heart looping.…”
Section: Discussionmentioning
confidence: 99%
“…Organ culture of incisor tooth germs of mice Explants containing incisor tooth germs of the lower incisor were obtained from mandibles of E14.5 mice and cultured in a modified Trowell's system for periods of up to 11 days as described elsewhere (Tabata et al 1996;Liu et al 2000). Explants were cultured in BGJb medium (Fitton-Jackson's modified BGJ; Gibco BRL, Gaithersburg, USA), containing 100 µg/ml ascorbic acid (Nakai Chemical, Kyoto, Japan) and 100 U/ml penicillin-streptomycin (Gibco BRL).…”
Section: Animalsmentioning
confidence: 99%
“…In humans, abnormal crown patterns in patients with congenital syphilis have been ascribed to result from infection of the tooth follicle (3). Likewise, loss of function of parathyroid hormone-related protein (PTHrP) leads to loss of alveolar bone resorption and deformation of the tooth crown in the mouse (15)(16)(17)(18)(19). A lethal human syndrome called Blomstrand chondrodysplasia, which involves a loss of function of the receptor for PTHrP, results in a severe deformation of the base of a tooth crown due to an excess of bone formation (20).…”
mentioning
confidence: 99%
“…Cultured explants were fixed with 4% paraformaldehyde in a 0.1 M cacodylate buffer (pH 7.3) at 4 for 30 min -overnight, dehydrated through up-graded alcohols, deposited (Tabata et al, 1996a(Tabata et al, , 2002Liu et al, 2000;Shibaguchi et al, 2003).…”
Section: Light Microscopymentioning
confidence: 99%